Polarizing plate with retardation layer and image display device including same
By using adhesive to layer the resin film on the orientation curing layer of the liquid crystal compound, the problem that polarizers with phase difference layers are prone to dents when bonding to the image display panel, and higher stability is achieved and quality.
Patent Information
- Application Number
- CN202411054935.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-02
- Filing Date
- 2024-08-02
- Publication Date
- 2025-02-14
AI Technical Summary
When the polarizer with a phase difference layer is bonded to the image display panel, dents are easily generated on the visual recognition side, especially the orientation cured layer of the liquid crystal compound is thinner and dents are easily generated compared to the resin film.
A resin film is laminated on the orientation curing layer of the liquid crystal compound by means of the adhesive layer. The resin film can be laminated on the second adhesive layer side or the first adhesive layer side of the phase difference layer to enhance the stability of the polarizer. .
By this method, the generation of dents when bonding to the image display panel can be effectively suppressed, and the quality and reliability of the polarizer with a phase difference layer can be improved.
Smart Images

Figure CN119439349A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a polarizing plate with a phase difference layer and an image display device having the polarizing plate with a phase difference layer. Background Art
[0002] Image display devices represented by liquid crystal display devices and electroluminescent (EL) display devices (such as organic EL display devices and inorganic EL display devices) are rapidly becoming popular. In these image display devices, a polarizing plate with a phase difference layer is used for the purpose of improving display characteristics and preventing reflection. The polarizing plate with a phase difference layer can usually be laminated on the image display panel with the aid of an adhesive layer. A substrate and wiring are arranged on the surface of the image display panel.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2022-14611 Summary of the invention
[0006] Problems to be solved by the invention
[0007] When a polarizer with a phase difference layer is attached to an image display panel, a dent is sometimes generated on the visual recognition side of the polarizer with a phase difference layer (i.e., the side that does not contact the image display device). The thickness of the orientation solidified layer of the liquid crystal compound, i.e., the phase difference layer, is thinner than the phase difference layer made of a resin film, so there is a tendency to easily generate dents. Furthermore, for a polarizer with a phase difference layer in which the phase difference layer is sandwiched by an adhesive layer, the generation of dents may become more significant.
[0008] Means for solving problems
[0009] 1. The polarizing plate with a phase difference layer according to an embodiment of the present invention comprises, in order: a polarizing plate including a polarizer, a first adhesive layer, an orientation solidified layer of a liquid crystal compound, namely a phase difference layer, and a second adhesive layer, on which a resin film is laminated via an adhesive layer.
[0010] 2. In the polarizing plate with a retardation layer according to 1 above, the resin film may be laminated on the second pressure-sensitive adhesive layer side of the retardation layer.
[0011] 3. In the polarizing plate with a retardation layer according to 1 above, the resin film may be laminated on the first adhesive layer side of the retardation layer.
[0012] 4. In the polarizing plate with a retardation layer according to any one of 1 to 3 above, the resin film may be a cyclic olefin-based resin film.
[0013] 5. In the polarizing plate with a retardation layer according to any one of 1 to 4 above, the resin film may have a refractive index distribution of nx=ny>nz.
[0014] 6. In the polarizing plate with a phase difference layer described in any one of 1 to 5 above, the Re(550) of the phase difference layer can be 100nm~190nm, Re(450) / Re(550) can be <1, and the angle between the slow axis of the phase difference layer and the absorption axis of the polarizer can be 40°~50°.
[0015] 7. The polarizing plate with a retardation layer according to any one of 1 to 6 above may further include a retardation layer having a refractive index distribution of nz>nx=ny.
[0016] 8. In another aspect of the present invention, there is provided an image display device comprising the polarizing plate with a retardation layer according to any one of 1 to 7 above.
[0017] 9. The image display device described in 8 above may also be an organic electroluminescent display device.
[0018] Effects of the Invention
[0019] According to the embodiment of the present invention, a polarizing plate with a phase difference layer in which the generation of pits is suppressed can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a schematic cross-sectional view of a polarizing plate with a retardation layer according to one embodiment of the present invention.
[0021] Figure 2 This is a schematic cross-sectional view of a polarizing plate with a retardation layer according to another embodiment of the present invention.
[0022] Figure 3 This is a schematic cross-sectional view of a polarizing plate with a retardation layer according to still another embodiment of the present invention.
[0023] Figure 4 This is a schematic cross-sectional view of a polarizing plate with a retardation layer according to still another embodiment of the present invention.
[0024] Description of Reference Numerals
[0025] 10 Polarizer
[0026] 11 Polarizer
[0027] 12. Protective layer
[0028] 13. Protective layer
[0029] 20 first adhesive layer
[0030] 30 Phase difference layer
[0031] 31. First phase difference layer
[0032] 32 Second phase difference layer
[0033] 40 Adhesive layer
[0034] 50 Resin film
[0035] 60 Second adhesive layer
[0036] 100 Polarizing film with phase difference layer DETAILED DESCRIPTION
[0037] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these embodiments.
[0038] (Definition of terms and symbols)
[0039] The definitions of terms and symbols in this specification are as follows.
[0040] (1) Refractive index (nx, ny, nz)
[0041] “nx” is the refractive index in the direction where the refractive index in the plane is maximum (ie, the slow axis direction), “ny” is the refractive index in the direction orthogonal to the slow axis in the plane (ie, the fast axis direction), and “nz” is the refractive index in the thickness direction.
[0042] (2) In-plane phase difference (Re)
[0043] "Re(λ)" is the in-plane phase difference measured at 23°C using light of wavelength λnm. For example, "Re(550)" is the in-plane phase difference measured at 23°C using light of wavelength 550nm. Re(λ) is calculated by the formula: Re(λ) = (nx-ny) × d, when the thickness of the layer (thin film) is d (nm).
[0044] (3) Retardation in the thickness direction (Rth)
[0045] "Rth(λ)" is the phase difference in the thickness direction measured at 23°C using light of wavelength λnm. For example, "Rth(550)" is the phase difference in the thickness direction measured at 23°C using light of wavelength 550nm. Rth(λ) is calculated by the formula: Rth(λ) = (nx-nz) × d, when the thickness of the layer (film) is d (nm).
[0046] (4) Nz coefficient
[0047] The Nz coefficient is obtained by Nz=Rth / Re.
[0048] (5) Angle
[0049] When an angle is mentioned in this specification, the angle includes both clockwise and counterclockwise relative to a reference direction. Therefore, for example, "45°" means ±45°.
[0050] A. Overall structure of polarizing plate with phase difference layer
[0051] Figure 1 It is a schematic cross-sectional view of a polarizing plate with a phase difference layer according to an embodiment of the present invention. The polarizing plate with a phase difference layer shown in the figure has a polarizing plate 10 including a polarizer 11, a first adhesive layer 20, a phase difference layer 30, an adhesive layer 40, a resin film 50, and a second adhesive layer 60 in sequence. The phase difference layer 30 is laminated with the resin film 50 by means of the adhesive layer 40. In the example shown in the figure, the resin film 50 is laminated on the second adhesive layer 60 side of the phase difference layer 30 by means of the adhesive layer 40, but the resin film 50 can also be laminated on the first adhesive layer 20 side of the phase difference layer 30 by means of the adhesive layer 40. The polarizing plate 10 typically includes a polarizer 11 and protective layers 12 and 13 arranged on both sides of the polarizer 11. The protective layer 13 can also be omitted. For example, in the case where the phase difference layer can also function as a protective layer, the protective layer 13 can also be omitted. The phase difference layer 30 is an orientation solidification layer of a liquid crystal compound (hereinafter also referred to as a liquid crystal orientation solidification layer). The phase difference layer 30 may be only one layer or may include two or more layers. In the case of including two or more phase difference layers, at least one phase difference layer may be a liquid crystal orientation solidification layer. In this embodiment, a resin film may be laminated on the liquid crystal orientation solidification layer, i.e., the phase difference layer, by means of an adhesive layer. Figure 2 Schematic cross-sectional view of a polarizer with a phase difference layer according to another embodiment of the present invention. The polarizer with a phase difference layer in the illustrated example has a polarizer 10, a first adhesive layer 20, a first phase difference layer 31, an adhesive layer 41, a second phase difference layer 32, an adhesive layer 42, a resin film 50, and a second adhesive layer 60 in sequence. In the illustrated example, the second phase difference layer 32 is a liquid crystal orientation solidification layer. In the illustrated example, the resin film 50 is laminated on the second adhesive layer 60 side of the second phase difference layer 32 by means of the adhesive layer 42. Figure 3 Schematic cross-sectional view of a polarizing plate with a retardation layer according to another embodiment of the present invention. In the example shown in the figure, the first retardation layer 31 is a liquid crystal alignment solidification layer. In the example shown in the figure, the resin film 50 is laminated on the first adhesive layer side of the first retardation layer 31 via the adhesive layer 41. Figure 4It is a schematic cross-sectional view of a polarizer with a phase difference layer according to another embodiment of the present invention. In the example shown in the figure, the first phase difference layer 31 and the second phase difference layer 32 are both liquid crystal orientation solidification layers. In the example shown in the figure, the resin film 50 is laminated on the second adhesive layer 60 side of the first phase difference layer 31 by means of an adhesive layer 41. In addition, the resin film 50 is laminated on the first adhesive layer 20 side of the second phase difference layer 32 by means of an adhesive layer 42. In the case where the resin film is bonded to components other than the phase difference layer, it can be laminated by means of an adhesive layer or by means of an adhesive layer. As described above, in the case of a liquid crystal orientation solidification layer, i.e., a phase difference layer, more than two layers of liquid crystal orientation solidification layers, as long as a resin film is laminated on at least one phase difference layer by means of an adhesive layer. In the example shown in the figure, there is one resin film, but more than two layers of resin films may also be included. In a polarizer with a phase difference layer including a liquid crystal orientation solidification layer, i.e., a phase difference layer, the generation of dents when bonded to an image display panel may become a problem. In addition, in a polarizer with a phase difference layer in which the phase difference layer is sandwiched by an adhesive layer, the generation of dents may become more significant. A substrate and wiring are arranged on the surface of one side of the polarizer with a phase difference layer stacked on the image display panel, and the surface may have concave and convex. The concave and convex may be a cause of the dents of the polarizer with a phase difference layer. In the polarizer with a phase difference layer of an embodiment of the present invention, a resin film is stacked on the liquid crystal orientation solidification layer, that is, the phase difference layer, with the aid of an adhesive layer. If it is such a polarizer with a phase difference layer, the generation of dents when attached to the image display panel can be suppressed.
[0052] As described above, the polarizer 100 with a phase difference layer may have a second adhesive layer 60 as the outermost layer. The polarizer 100 with a phase difference layer may be attached to an image display device (substantially an image display panel) by means of the second adhesive layer 60. In practice, it is preferred that a release liner is temporarily bonded to the surface of the second adhesive layer 60 until the polarizer with a phase difference layer is used. By temporarily bonding the release liner, the adhesive layer is protected until the actual use, and the roll-up of the polarizer with a phase difference layer is possible.
[0053] The thickness of the polarizer with a phase difference layer can be set to any appropriate value. In one embodiment, the total thickness of the polarizer with a phase difference layer is preferably 150 μm or less, more preferably 140 μm or less, further preferably 120 μm or less, more preferably 100 μm or less, further more preferably 90 μm or less, and particularly preferably 85 μm or less. The total thickness of the polarizer with a phase difference layer can be, for example, 30 μm or more. It should be noted that the total thickness of the polarizer with a phase difference layer refers to the total thickness of the polarizer, the first adhesive layer, the phase difference layer, the adhesive layer, the resin film, and the second adhesive layer (that is, the total thickness of the polarizer with a phase difference layer does not include the thickness of the release liner that can be temporarily bonded to the surface of the second adhesive layer).
[0054] Hereinafter, the components of the polarizing plate with a retardation layer will be described in more detail.
[0055] B. Polarizer
[0056] B-1. Polarizer
[0057] The polarizer is typically composed of a resin film containing a dichroic substance (typically iodine). As the resin film, any appropriate resin film that can be used as a polarizer can be used. The resin film is typically a polyvinyl alcohol resin (hereinafter referred to as "PVA resin") film. The resin film can be a single-layer resin film or a laminate of two or more layers.
[0058] As a specific example of a polarizer composed of a single-layer resin film, a polarizer in which a PVA-based resin film has been subjected to a dyeing treatment and a stretching treatment (representatively uniaxial stretching) using iodine can be cited. The above-mentioned dyeing using iodine is performed, for example, by immersing the PVA-based resin film in an iodine aqueous solution. The stretching ratio of the above-mentioned uniaxial stretching is preferably 3 to 7 times. Stretching can be performed after the dyeing treatment, or it can be performed while dyeing. In addition, dyeing can also be performed after stretching. As needed, the PVA-based resin film is subjected to a swelling treatment, a cross-linking treatment, a cleaning treatment, a drying treatment, etc. For example, by immersing the PVA-based resin film in water for washing before dyeing, not only can the dirt and anti-blocking agent on the surface of the PVA-based resin film be cleaned, but also the PVA-based resin film can be swelled to prevent uneven dyeing.
[0059] As a specific example of a polarizer obtained using a laminate, there can be cited a polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer (PVA-based resin film) laminated on the resin substrate, or a polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate. The polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate can be made, for example, in the following manner: a PVA-based resin solution is applied to a resin substrate, dried to form a PVA-based resin layer on the resin substrate, and a laminate of the resin substrate and the PVA-based resin layer is obtained; the laminate is stretched and dyed to make the PVA-based resin layer into a polarizer. In the present embodiment, a polyvinyl alcohol-based resin layer containing a halide and a polyvinyl alcohol-based resin is preferably formed on one side of the resin substrate. Stretching typically includes immersing the laminate in a boric acid aqueous solution for stretching. Furthermore, the stretching may further include stretching the laminate in the air at a high temperature (e.g., above 95°C) before stretching in a boric acid aqueous solution as needed. Furthermore, in the present embodiment, it is preferred that the laminate is subjected to a drying shrinkage treatment in which the laminate is shrunk by more than 2% in the width direction by heating while being transported in the length direction. Typically, the manufacturing method of the present embodiment includes sequentially performing an air auxiliary stretching treatment, a dyeing treatment, an underwater stretching treatment, and a drying shrinkage treatment on the laminate. By introducing auxiliary stretching, the crystallinity of the PVA can be improved even when the PVA is coated on the thermoplastic resin, and high optical properties can be achieved. In addition, by simultaneously improving the orientation of the PVA in advance, when immersed in water in the subsequent dyeing process and the stretching process, problems such as the reduction and dissolution of the orientation of the PVA can be prevented, and high optical properties can be achieved. Furthermore, when the PVA-based resin layer is immersed in a liquid, the disorder of the orientation and the reduction of the orientation of the polyvinyl alcohol molecules can be suppressed compared to the case where the PVA-based resin layer does not contain a halide. Thus, the optical properties of the polarizer obtained by the treatment process of immersing the laminate in a liquid such as a dyeing treatment and an underwater stretching treatment can be improved. Furthermore, by shrinking the laminate in the width direction using a drying shrinkage treatment, the optical properties can be improved. The obtained laminate of resin substrate / polarizer can be used directly (that is, the resin substrate can be used as a protective layer of polarizer), or the resin substrate can be peeled off from the laminate of resin substrate / polarizer, and any appropriate protective layer used according to the purpose can be stacked on the peeling surface for use. The details of the manufacturing method of such a polarizer are, for example, recorded in Japanese Patent Publication No. 2012-73580 (Japanese Patent No. 5414738) and Japanese Patent No. 6470455. For these publications, the entire records are cited in this specification as a reference.
[0060] The thickness of the polarizer is preferably 1 to 30 μm, more preferably 1 to 25 μm, further preferably 1 to 15 μm, further more preferably 1 to 10 μm, and particularly preferably 1 to 8 μm. If the thickness of the polarizer is within the above range, the polarizing plate with a retardation layer can be made thinner.
[0061] The polarizer preferably shows absorption dichroism at any wavelength between 380nm and 780nm. The single transmittance Ts of the polarizer is preferably 40% to 48%, more preferably 41% to 46%. The polarization degree P of the polarizer is preferably 97.0% or more, more preferably 99.0% or more, and further preferably 99.9% or more. The above single transmittance is typically the Y value measured using an ultraviolet visible spectrophotometer and corrected for sensitivity. The above polarization degree is typically obtained by the following formula based on the parallel transmittance Tp and the orthogonal transmittance Tc measured using an ultraviolet visible spectrophotometer and corrected for sensitivity.
[0062] Polarization degree (%) = {(Tp-Tc) / (Tp+Tc)} 1 / 2 ×100
[0063] B-2. Protective layer
[0064] The protective layers 12 and 13 are formed by any appropriate film that can be used as a protective layer of a polarizer. As a specific example of the material that becomes the main component of the film, cellulose resins such as triacetyl cellulose (TAC), polyester resins, polyvinyl alcohol resins, polycarbonate resins, polyamide resins, polyimide resins, polyethersulfone resins, polysulfone resins, polystyrene resins, polynorbornene resins, polyolefin resins, (meth) acrylic resins, acetate resins, etc. can be listed. In addition, thermosetting resins or ultraviolet curing resins such as (meth) acrylic resins, carbamate resins, (meth) acrylic acid carbamate resins, epoxy resins, silicone resins, etc. can also be listed. In addition, for example, glassy polymers such as siloxane polymers can also be listed. In addition, the polymer film described in Japanese Patent Publication No. 2001-343529 (WO 01 / 37007) can also be used. As the material of the film, for example, a resin composition containing a thermoplastic resin having a substituted or unsubstituted imide group in the side chain and a thermoplastic resin having a substituted or unsubstituted phenyl group and a nitrile group in the side chain can be used, for example, a resin composition having an alternating copolymer formed by isobutylene and N-methylmaleimide and an acrylonitrile-styrene copolymer can be listed. The polymer film can be, for example, an extrusion molding of the above resin composition.
[0065] The polarizing plate with a retardation layer is typically disposed on the visual recognition side of the image display device, and the protective layer 12 is typically disposed on the visual recognition side thereof. Therefore, the protective layer 12 may be subjected to surface treatment such as hard coating, anti-reflection treatment, anti-sticking treatment, anti-glare treatment, etc. as needed.
[0066] The thickness of the protective layer is preferably 10 μm to 50 μm, more preferably 10 μm to 30 μm. When surface treatment is performed, the thickness of the outer protective layer (protective layer 12 ) is the thickness including the thickness of the surface treatment layer.
[0067] C. Phase difference layer
[0068] The phase difference layer includes a liquid crystal orientation solidification layer, i.e., a phase difference layer. As described above, when the phase difference layer is a liquid crystal orientation solidification layer, the dents when attached to the image display panel may become more significant. In an embodiment of the present invention, a resin film is laminated on the liquid crystal orientation solidification layer, i.e., the phase difference layer, with the aid of an adhesive layer. If it is a polarizer with a phase difference layer laminated with a resin film with the aid of an adhesive layer, the generation of dents when attached to the image display panel can be suppressed. The phase difference layer may be only one layer or may include two or more layers. In the case of a phase difference layer including two or more layers, as long as at least one phase difference layer is a liquid crystal orientation solidification layer, all phase difference layers contained in the polarizer with a phase difference layer may be liquid crystal orientation solidification layers.
[0069] In one embodiment, the phase difference layer can function as a λ / 4 plate. The phase difference layer can be a single layer or a laminate of two or more layers. The phase difference layer can further include an orientation layer and / or a substrate.
[0070] In one embodiment, the phase difference layer is a single layer. The first phase difference layer preferably has Re(550) of 100nm to 190nm, Re(450) / Re(550) of the phase difference layer is <1, and the angle between the slow axis of the first phase difference layer and the absorption axis of the polarizer is 40° to 50°. The in-plane phase difference Re(550) of the phase difference layer is preferably 100nm to 190nm, more preferably 110nm to 170nm, and further preferably 130nm to 160nm.
[0071] In this embodiment, the Nz coefficient of the retardation layer is preferably 0.9 to 1.5, and more preferably 0.9 to 1.3. If such a relationship is satisfied, when the obtained polarizing plate with a retardation layer is used in an image display device, a very excellent reflection hue can be achieved.
[0072] The thickness of the retardation layer is preferably 10 μm or less, more preferably 0.5 μm to 10 μm, further preferably 0.5 μm to 7 μm, and particularly preferably 1 μm to 5 μm.
[0073] The phase difference layer preferably exhibits inverse dispersion wavelength characteristics. At this time, Re(550) / Re(650) is preferably greater than 1, more preferably greater than 1 and less than 1.2, and further preferably 1.01 to 1.15. In addition, Re(450) / Re(550) of the phase difference layer is preferably less than 1, more preferably greater than 0.8 and less than 1, and further preferably greater than 0.8 and less than 0.95. If such a structure is used, very excellent anti-reflection properties can be achieved.
[0074] In this embodiment, the angle between the slow axis of the phase difference layer and the absorption axis of the polarizer is preferably 40° to 50°, more preferably 42° to 48°, and further preferably about 45°. If the angle is in such a range, by making the phase difference layer a λ / 4 plate, a polarizing plate with a phase difference layer having very excellent circular polarization characteristics (resulting in very excellent anti-reflection characteristics) can be obtained.
[0075] As described above, the phase difference layer is an oriented solidified layer of a liquid crystal compound. By using a liquid crystal compound, the difference between nx and ny of the phase difference layer obtained can be significantly increased compared to non-liquid crystal materials, so the thickness of the phase difference layer for obtaining the desired in-plane phase difference can be significantly reduced. As a result, the polarizer with a phase difference layer can be further thinned.
[0076] The orientation solidification layer of the liquid crystal compound, i.e., the phase difference layer, can be formed using a composition containing a polymerizable liquid crystal compound. In this specification, the polymerizable liquid crystal compound contained in the composition refers to a compound having a polymerizable group and having liquid crystal properties. A polymerizable group refers to a group that participates in a polymerization reaction, preferably a photopolymerizable group. Here, a photopolymerizable group refers to a group that can participate in a polymerization reaction through an active free radical, an acid, etc. generated by a photopolymerization initiator.
[0077] The expression of liquid crystal properties can be thermotropic or lyotropic. In addition, as the composition of the liquid crystal phase, it can be a nematic liquid crystal or a smectic liquid crystal. From the perspective of ease of manufacture, it is preferred that the liquid crystal properties are thermotropic nematic liquid crystals. Details of the phase difference layer as such a liquid crystal orientation solidification layer are described, for example, in Japanese Patent Laid-Open No. 2023-75790 Gazette, etc. The entirety of the gazette is cited in this specification as a reference.
[0078] In one embodiment, the polarizer with a phase difference layer may further include other phase difference layers (also referred to as second phase difference layers). Other phase difference layers may be stretched films of polymer films or liquid crystal orientation solidification layers. Other phase difference layers may be so-called positive C plates whose refractive index characteristics show the relationship of nz>nx=ny. If a positive C plate is used as another phase difference layer, reflection in the tilted direction can be well prevented, and a wide viewing angle of the anti-reflection function can be achieved. According to an embodiment of the present invention, even when a liquid crystal orientation solidification layer is used as another phase difference layer, the generation of dents when attached to an image display panel can be suppressed. The phase difference Rth(550) in the thickness direction of the liquid crystal orientation solidification layer, i.e., another phase difference layer, is preferably -50nm to -300nm, more preferably -70nm to -250nm, further preferably -90nm to -200nm, and particularly preferably -100nm to -180nm. Here, "nx=ny" includes not only the case where nx is strictly equal to ny, but also the case where nx is substantially equal to ny. That is, the in-plane retardation Re(550) of the liquid crystal alignment solidification layer, ie, other retardation layer, may be smaller than 10 nm.
[0079] The liquid crystal orientation solidification layer having the refractive index characteristic of nz>nx=ny can be formed by any appropriate material. It is preferably composed of a film containing a liquid crystal material fixed to a vertical orientation. The liquid crystal material (liquid crystal compound) capable of vertical orientation can be a liquid crystal monomer or a liquid crystal polymer. As a specific example of the method for forming the liquid crystal compound and the phase difference layer, the liquid crystal compound and the method for forming the phase difference layer described in
[0020] to
[0028] of Japanese Patent Gazette No. 2002-333642 can be cited. At this time, the thickness of the other phase difference layer is preferably 0.5μm to 10μm, more preferably 0.5μm to 8μm, and further preferably 0.5μm to 5μm.
[0080] D. Resin film
[0081] As the resin film, any appropriate resin film can be used. As described above, if a resin film is laminated on the liquid crystal orientation solidification layer, i.e., the phase difference layer, by means of an adhesive layer, the generation of dents when attached to the image display panel can be suppressed. As the resin constituting the resin film, any appropriate resin can be used. For example, cyclic olefin resins such as norbornene resin, acrylic resins, polycarbonate resins, cellulose resins, etc. can be listed. Norbornene resin is preferably used. Only one resin can be used, or two or more can be used in combination. In addition, the resin film can be a single film or a laminate of more than two layers. The resin film is preferably unstretched (unstretched resin film).
[0082] The thickness of the resin film can be set to any appropriate value. The thickness of the resin film is preferably 1 μm to 40 μm, more preferably 3 μm to 30 μm, and further preferably 5 μm to 20 μm. If the thickness of the resin film is within the above range, the generation of dents when attached to an image display panel can be suppressed.
[0083] The resin film may have any appropriate refractive index distribution. In one embodiment, the resin film may preferably be a so-called negative C plate having a refractive index distribution satisfying nx=ny>nz. If the resin film is a negative C plate, a polarizing plate with a phase difference layer having excellent image display properties can be provided.
[0084] The smaller the in-plane phase difference Re(550) of the resin film, the more preferred. The in-plane phase difference Re(550) of the resin film is preferably 20 nm or less, more preferably 15 nm or less, further preferably 10 nm or less, and particularly preferably 5 nm or less. If the in-plane phase difference Re(550) of the resin film is within the above range, a polarizing plate with a phase difference layer having excellent image display characteristics can be provided. The in-plane phase difference Re(550) is, for example, 0 nm or more.
[0085] The smaller the absolute value of the phase difference Rth (550) in the thickness direction of the resin film, the more preferred. The absolute value of the phase difference Rth (550) in the thickness direction of the resin film is preferably less than 20nm, more preferably less than 15nm, further preferably less than 10nm, and particularly preferably less than 5nm. If the absolute value of the phase difference Rth (550) in the thickness direction of the resin film is within the above range, a polarizing plate with a phase difference layer having excellent image display characteristics can be provided. The absolute value of the phase difference Rth (550) in the thickness direction is, for example, greater than 0nm.
[0086] The total light transmittance of the resin film is preferably 80% or more, more preferably 85% or more, and further preferably 90% or more. The total light transmittance of the resin film is, for example, 99% or less. If the total light transmittance of the resin film is within the above range, a polarizing plate with a phase difference layer having excellent image display properties can be provided. The total light transmittance of the resin film can be measured according to JIS K 7361.
[0087] The haze of the resin film is preferably 10% or less, more preferably 5% or less, further preferably 1% or less, and particularly preferably 0.5% or less. The haze is, for example, 0.1% or more. If the haze of the resin film is within the above range, a polarizing plate with a phase difference layer having excellent image display properties can be provided. The haze of the resin film can be measured according to JIS K 7361.
[0088] The tensile modulus of the resin film is preferably 1000 MPa to 3000 MPa, more preferably 1200 MPa to 2500 MPa, and further preferably 1500 MPa to 2000 MPa. If the tensile modulus of the resin film is within the above range, the generation of dents when attached to an image display panel can be suppressed. The tensile modulus of the resin film can be measured at room temperature (23° C.) according to JIS K 7161.
[0089] The tensile strength at break of the resin film is preferably 0.5N to 20N, more preferably 1N to 15N, and further preferably 3N to 12N. If the tensile strength at break of the resin film is within the above range, the generation of dents when attached to an image display panel can be suppressed. The tensile strength at break of the resin film can be measured at room temperature (23° C.) according to JIS K 7161.
[0090] The elongation at break of the resin film is preferably 1% to 10%, more preferably 2% to 8%, and further preferably 3% to 7%. If the elongation at break of the resin film is within the above range, the generation of dents when attached to an image display panel can be suppressed. The elongation at break of the resin film can be measured by using a thermomechanical analyzer (TMA).
[0091] The moisture permeability of the resin film is preferably 20 g / m 2 / 24 hours~60g / m 2 / 24 hours, more preferably 25g / m 2 / 24 hours~50g / m 2 / 24 hours, more preferably 30g / m 2 / 24 hours~40g / m 2 When the moisture permeability of the resin film is within the above range, the generation of dents when attached to an image display panel can be suppressed. The moisture permeability of the resin film can be measured under the conditions of a temperature of 40° C. and a humidity of 92% RH in accordance with JIS Z 0208.
[0092] E. Adhesive layer
[0093] The first adhesive layer and the second adhesive layer can be formed by any appropriate adhesive. As the specific example of the adhesive constituting the adhesive layer, acrylic adhesive, rubber adhesive, silicone adhesive, polyester adhesive, urethane adhesive, epoxy adhesive, and polyether adhesive can be listed. By adjusting the type, quantity, combination and blending ratio of the monomers of the base resin forming the adhesive, as well as the blending amount, reaction temperature, reaction time, etc. of the crosslinking agent, an adhesive with the desired characteristics corresponding to the purpose can be prepared. The base resin of the adhesive can only use one, or more than two can be used in combination. The first adhesive layer and the second adhesive layer can be formed by the same adhesive, or they can be formed by different adhesives. From the viewpoints of transparency, processability and durability, acrylic adhesive (acrylic adhesive composition) is preferred.
[0094] The acrylic adhesive typically contains a (meth)acrylic polymer as a main component. The (meth)acrylic polymer may be contained in the adhesive in a proportion of, for example, 50% by weight or more, preferably 70% by weight or more, and more preferably 90% by weight or more, in the solid content of the adhesive.
[0095] The (meth)acrylic polymer contains an alkyl (meth)acrylate as a monomer unit as a main component. In addition, (meth)acrylate refers to acrylate and / or methacrylate. The alkyl (meth)acrylate may be contained in the monomer component forming the (meth)acrylic polymer preferably in a ratio of 80% by weight or more, more preferably in a ratio of 90% by weight or more. As the alkyl group of the alkyl (meth)acrylate, for example, a linear or branched alkyl group having 1 to 18 carbon atoms can be cited. The average number of carbon atoms of the alkyl group is preferably 3 to 9, more preferably 3 to 6.
[0096] The acrylic adhesive may preferably contain a silane coupling agent and / or a crosslinking agent. As the silane coupling agent, for example, an epoxy-containing silane coupling agent may be cited. As the crosslinking agent, for example, an isocyanate crosslinking agent and a peroxide crosslinking agent may be cited. Furthermore, the acrylic adhesive composition may contain an antioxidant and / or a conductive agent. The details of the adhesive layer or the acrylic adhesive composition are, for example, described in Japanese Patent Publication No. 2006-183022, Japanese Patent Publication No. 2015-199942, Japanese Patent Publication No. 2018-053114, Japanese Patent Publication No. 2016-190996, and International Publication No. 2018 / 008712, and the records of these publications are cited in this specification as reference.
[0097] The thickness of the adhesive layer can be set to any appropriate value. The thickness of the first adhesive layer is preferably 2 μm to 50 μm, more preferably 3 μm to 30 μm, and further preferably 5 μm to 15 μm. In addition, the thickness of the second adhesive layer is preferably 10 μm to 100 μm, more preferably 15 μm to 70 μm, and further preferably 20 μm to 50 μm. When the thickness of the adhesive layer is within the above range, the adhesion of each component can be fully ensured.
[0098] F. Adhesive layer
[0099] The adhesive layer may be formed of any appropriate adhesive. For example, an active energy ray-curable adhesive may be used. As the active energy ray-curable adhesive, any appropriate active energy ray-curable adhesive may be used, for example, an ultraviolet-curable adhesive and an electron beam-curable adhesive may be listed.
[0100] Active energy ray curing adhesives typically contain monofunctional components, multifunctional components (curing components) and photopolymerization initiators. The monofunctional components and multifunctional components are each typically free radical polymerizable compounds. As preferred monofunctional components, for example, higher alkyl esters of (meth) acrylic acid and modified bodies thereof can be listed. Specifically, isostearyl acrylate, lauryl acrylate, acryloyl morpholine, unsaturated fatty acid hydroxyalkyl ester modified ε-caprolactone, etc. can be listed. As preferred multifunctional components, for example, monomers and / or oligomers having more than two functional groups such as (meth) acrylate groups and (meth) acrylamide groups can be listed. Specifically, polyethylene glycol diacrylate, trimethylolpropane triacrylate, and glycerol triacrylate can be listed. As a specific example of a monofunctional component or a multifunctional component other than the above, tripropylene glycol diacrylate, 1,9-nonanediol diacrylate, tricyclodecane dimethanol diacrylate, phenoxydiethylene glycol acrylate, cyclic trimethylolpropane formal acrylate, dioxanediol diacrylate, EO modified diglycerol tetraacrylate, γ-butyrolactone acrylate, N-methylpyrrolidone, hydroxyethyl acrylamide, N-hydroxymethyl acrylamide, N-methoxymethyl acrylamide, N-ethoxymethyl acrylamide, 9-vinyl carbazole can be listed. In one embodiment, the monofunctional component or the multifunctional component has a ring structure. Specifically, acryloyl morpholine, γ-butyrolactone acrylate, unsaturated fatty acid hydroxyalkyl ester modified ε-caprolactone, N-methylpyrrolidone, and 9-vinyl carbazole can be listed. The monofunctional component or the multifunctional component can be used only one kind, respectively, or two or more kinds can be used in combination.
[0101] The active energy ray-curable adhesive may further contain a cationic polymerizable compound as needed. The cationic polymerizable compound may be monofunctional or polyfunctional. As monofunctional cationic polymerizable compounds, for example, p-tert-butylphenyl glycidyl ether and 3-ethyl-3-[(2-ethylhexyl)oxy]oxetane may be listed. As polyfunctional cationic polymerizable compounds, for example, 3-ethyl-3-{[(3-ethyloxetane-3-yl)methoxy]methyl}oxetane may be listed. As cationic polymerizable compounds, a silane coupling agent may be used. As a silane coupling agent, for example, 3-glycidoxypropyltrimethoxysilane may be listed.
[0102] The active energy ray-curable adhesive may further contain any appropriate additives, such as a plasticizer (for example, an oligomer component), a crosslinking agent, a diluent, etc. These additives may be used in any appropriate content according to the purpose.
[0103] The details of the active energy ray-curable adhesive are described in, for example, Japanese Patent Application Laid-Open No. 2018-017996. The description of the publication is incorporated herein by reference.
[0104] The thickness of the adhesive layer is preferably 0.3 μm to 3 μm, more preferably 0.6 μm to 2 μm, and further preferably 0.9 μm to 1.5 μm. When the thickness of the adhesive layer is within the above range, the retardation layer and the resin film can be appropriately adhered to each other.
[0105] G. Image display device
[0106] The polarizer with a phase difference layer described in the above items A to F can be applied to an image display device. Therefore, an embodiment of the present invention includes an image display device using such a polarizer with a phase difference layer. As a representative example of an image display device, a liquid crystal display device and an electroluminescent (EL) display device (such as an organic EL display device, an inorganic EL display device) can be listed. The image display device of an embodiment of the present invention can have the above-mentioned polarizer with a phase difference layer on its visual recognition side. The polarizer with a phase difference layer can be stacked in a manner that the phase difference layer becomes the side of the image display unit (such as a liquid crystal unit, an organic EL unit, an inorganic EL unit) (in a manner that the polarizer becomes the visual recognition side). As described above, the polarizer with a phase difference layer of an embodiment of the present invention can suppress the generation of dents when it is attached to the image display panel. Therefore, the productivity of the image display device can be improved.
[0107] Example
[0108] The present invention is specifically described below by way of examples, but the present invention is not limited to these examples. The measuring methods of various properties are as follows. It should be noted that, unless otherwise specified, the "parts" and "%" in the examples and comparative examples are by weight.
[0109] (1) Thickness
[0110] The thickness of 10 μm or less was measured using an interference film thickness meter (manufactured by Otsuka Electronics Co., Ltd., product name "MCPD-3000"), and the thickness exceeding 10 μm was measured using a digital micrometer (manufactured by Anritsu Co., Ltd., product name "KC-351C").
[0111] (2) Load resistance evaluation
[0112] The polarizer with a phase difference layer obtained in the embodiment and the comparative example is cut into 1 cm in length and 1 cm in width as a sample. The second adhesive layer of the sample is bonded to an aluminum sheet (aluminum reflective plate (Toray Advanced Film Co., Ltd., trade name "Cerapeel DMS-X42", total reflectivity: 86%)). Then, the surface of the hard coating side of the sample is placed on a glass plate (Matsunami Glass Ind., Ltd., thickness: 0.7 mm) in such a way that the surface is in contact with the glass plate. Then, a weight is placed on a conical indenter (diameter 1.5 mm) through a polyethylene terephthalate (PET) sheet (Toray, thickness 80 μm) from the aluminum sheet side and pressed for 10 seconds. The weight (load) of the weight is changed to 300 g (1.7 MPa), 400 g (2.2 MPa) and 500 g (2.8 MPa) for measurement. Then, remove the weight and the pressure head, and observe the surface of the polarizer with a phase difference layer in contact with the glass plate at a polar angle of 30° to 60° visual azimuth to confirm the presence or absence of dents, and take the maximum load at which no dents can be confirmed as the load resistance. It should be noted that when the surface of the polarizer with a phase difference layer is set as the X-axis and the Y-axis, and the axis orthogonal to the XY plane is set as the Z-axis, the angle inclined from the Z-axis to the XY plane direction is set as the polar angle (θ), the MD direction of the polarizer used in the polarizer with a phase difference layer is set to 0°, and the measurement angle specified as counterclockwise relative to the MD direction of the polarizer is set as the azimuth (φ) for evaluation.
[0113] (3) Reflection hue (hue at polar angle 45°)
[0114] The polarizer with phase difference layer obtained in the embodiment and comparative example was cut into 1 cm in length and 1 cm in width as a sample. The second adhesive layer of the sample was bonded to an aluminum reflector (Toray Advanced Film Co., Ltd., trade name "Cerapeel DMS-X42", total reflectivity: 86%). The case where there is a change in hue when observing the azimuth angle by reflection at a polar angle of 45° is set to 1, and the case where there is no change in hue is set to 2. Furthermore, the case where the hue is consistent with the azimuth angle even when observed at a polar angle of 0° is evaluated as 3.
[0115] (4)Judgment
[0116] The suitability as a polarizing plate with a retardation layer used in an image display device was evaluated based on the following criteria.
[0117] ○○ (Best): The load resistance exceeds 2 MPa in the indentation evaluation, and the reflection color is 3
[0118] ○ (Good): The load resistance evaluation exceeded 2 MPa, and the reflection color was 2
[0119] △ (OK): The load resistance exceeds 2MPa in the indentation evaluation, and the reflection color is 1
[0120] ×(Not allowed): The load resistance test is not more than 2MPa
[0121] [Manufacturing Example 1] Preparation of Adhesive Composition
[0122] 1. Preparation of base polymer
[0123] A monomer mixture containing 94.9 parts by weight of butyl acrylate (BA), 5 parts by weight of acrylic acid (AA), and 0.1 parts by weight of 2-hydroxyethyl acrylate (HEA) was placed in a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet tube, and a condenser. Next, 0.1 parts by weight of 2,2'-azobisisobutyronitrile as a polymerization initiator was added together with ethyl acetate relative to 100 parts by weight of the monomer mixture (solid content), and nitrogen was introduced while slowly stirring to replace the nitrogen atmosphere. The liquid temperature in the flask was maintained at around 55°C and a polymerization reaction was performed for 7 hours. Then, ethyl acetate was added to the obtained reaction solution to obtain a solution of a (meth)acrylic acid polymer with a weight average molecular weight of 2 million adjusted to a solid content concentration of 30%.
[0124] 2. Preparation of acrylic adhesive composition
[0125] An acrylic adhesive composition was prepared by adding 0.6 parts by weight of an isocyanate crosslinking agent (trimethylolpropane / toluene diisocyanate adduct, manufactured by Tosoh Corporation, trade name "CORONATE L") and 0.1 parts by weight of a silane coupling agent (trade name: KBM 403, manufactured by Shin-Etsu Chemical Co., Ltd.) to 100 parts by weight of the solid content of the obtained (meth)acrylic polymer solution.
[0126] [Manufacturing Example 2] Preparation of UV Curable Adhesive A
[0127] An ultraviolet curing adhesive A was prepared by mixing 50 parts by weight of unsaturated fatty acid hydroxyalkyl ester-modified ε-caprolactone (manufactured by Daicel, trade name "PLACCEL FA-1DDM"), 10 parts by weight of polyethylene glycol diacrylate (manufactured by Kyoeisha Chemical Co., Ltd., trade name "LIGHT ACRYLATE 9EG-A"), 20 parts by weight of acryloylmorpholine, 15 parts by weight of an acrylic polymer (manufactured by Toagosei Co., Ltd., trade name "ARUFONUP-1190"), 3 parts by weight of a photopolymerization initiator (manufactured by IGM Resins, product name "Omnirad 907"), and 2 parts by weight of a photopolymerization initiator (manufactured by Nippon Kayaku Co., Ltd., trade name "KAYACURE-DETX-S") .
[0128] [Example 1]
[0129] <Production of polarizing plate>
[0130] 1. Preparation of polarizer
[0131] As the thermoplastic resin substrate, a long amorphous polyethylene terephthalate copolymer film (thickness: 100 μm) having a Tg of about 75° C. was used, and one surface of the resin substrate was subjected to a corona treatment.
[0132] 13 parts by weight of potassium iodide was added to 100 parts by weight of a PVA-based resin prepared by mixing polyvinyl alcohol (degree of polymerization 4200, degree of saponification 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., trade name "GOHSEFIMER") in a ratio of 9:1, and the resulting substance was dissolved in water to prepare a PVA aqueous solution (coating liquid).
[0133] The PVA aqueous solution was applied to the corona-treated surface of the resin substrate and dried at 60° C. to form a PVA-based resin layer having a thickness of 13 μm, thereby producing a laminate.
[0134] The obtained laminate was uniaxially stretched to 2.4 times in the longitudinal direction (length direction) in an oven at 130° C. (in-air auxiliary stretching treatment).
[0135] Next, the laminate was immersed in an insolubilization bath (boric acid aqueous solution obtained by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (insolubilization treatment).
[0136] Next, the film was immersed in a dyeing bath (an iodine aqueous solution obtained by mixing iodine and potassium iodide at a weight ratio of 1:7 per 100 parts by weight of water) at a liquid temperature of 30° C. for 60 seconds while adjusting the concentration so that the single body transmittance (Ts) of the polarizer finally obtained would be a desired value (dyeing treatment).
[0137] Next, the sample was immersed in a crosslinking bath (boric acid aqueous solution prepared by mixing 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (crosslinking treatment).
[0138] Then, while the laminate is immersed in an aqueous boric acid solution (boric acid concentration 4 wt%, potassium iodide concentration 5 wt%) at a liquid temperature of 70°C, it is uniaxially stretched (underwater stretching treatment) in the longitudinal direction (length direction) between rollers with different peripheral speeds so that the total stretching ratio becomes 5.5 times.
[0139] Then, the laminated body was immersed in a cleaning bath (an aqueous solution prepared by mixing 4 parts by weight of potassium iodide with respect to 100 parts by weight of water) at a liquid temperature of 20° C. (cleaning treatment).
[0140] Thereafter, the film was dried in an oven maintained at approximately 90° C. while being brought into contact with a SUS heating roll maintained at a surface temperature of approximately 75° C. (drying shrinkage treatment).
[0141] In this manner, a polarizer having a thickness of 6 μm was formed on the resin substrate to obtain a polarizing plate having a structure of resin substrate / polarizer. The single-body transmittance Ts of the polarizer was 43.3%.
[0142] 2. Preparation of polarizer
[0143] On the surface of the obtained polarizer (the surface on the opposite side to the resin substrate), a HC-COP film is bonded with an ultraviolet curing adhesive. It should be noted that the HC-COP film is a film having a hard coating (HC) layer (thickness 4 μm) formed on a cycloolefin resin (COP) film (thickness 25 μm), and is bonded in such a way that the COP film becomes the polarizer side. It should be noted that the Re (550) of the COP film is 135 nm. Next, the resin substrate is peeled off, and a triacetyl cellulose (TAC) film (thickness 20 μm) is bonded to the peeled surface with the aid of an ultraviolet curing adhesive. As described above, a polarizer having the structure of HC layer / COP film (protective layer) / polarizer / TAC film (protective layer) is obtained.
[0144] <Manufacturing of Phase Difference Layer 1>
[0145] 55 parts by weight of the compound represented by formula (I), 25 parts by weight of the compound represented by formula (II) and 20 parts by weight of the compound represented by formula (III) were added to 400 parts by weight of cyclopentanone (CPN), and then heated to 60°C and stirred to dissolve. Then, the solution of the above compounds was returned to room temperature, 3 parts by weight of Irgacure 907 (manufactured by BASF Japan), 0.2 parts by weight of Megafac F-554 (manufactured by DIC Corporation) and 0.1 parts by weight of p-methoxyphenol (MEHQ) were added to the solution of the above compounds, and further stirred. The stirred solution was transparent and uniform. The obtained solution was filtered with a 0.20 μm membrane filter to obtain a polymerizable composition.
[0146] Separately, a polyimide solution for an alignment film was applied to a glass substrate having a thickness of 0.7 mm by spin coating, dried at 100° C. for 10 minutes, and fired at 200° C. for 60 minutes to obtain a coating film. The obtained coating film was rubbed using a commercially available rubbing device to form an alignment film.
[0147] Next, the polymerizable composition obtained above was applied to a substrate (substantially an alignment film) by spin coating and dried at 100° C. for 2 minutes. After the obtained coating film was cooled to room temperature, a high pressure mercury lamp was used to illuminate the film at 30 mW / cm 2 The liquid crystal compound was irradiated with ultraviolet light for 30 seconds to obtain an orientation solidified layer, i.e., a phase difference layer (thickness 1 μm). The in-plane phase difference Re(550) of the phase difference layer was 149 nm. In addition, the Re(450) / Re(550) of the phase difference layer was 0.851, showing an inverse dispersion wavelength characteristic.
[0148] The phase difference layer can function as a λ / 4 plate.
[0149]
[0150]
[0151] On the TAC film of the polarizer obtained above, an adhesive layer (first adhesive layer) with a thickness of 10 μm is formed using the adhesive obtained in Manufacturing Example 1. Then, the above-mentioned phase difference layer is bonded on the adhesive layer. It should be noted that the bonding is performed in a manner that the slow axis direction of the phase difference layer is at an angle of 45° clockwise relative to the absorption axis direction of the polarizer. Next, the adhesive obtained in Manufacturing Example 2 is applied to the phase difference layer in a manner to a thickness of 1 μm, and a resin film (manufactured by ZEON Corporation of Japan, trade name "ZEONOR FILM ZF14", thickness 13 μm) is bonded to the phase difference layer with the aid of an adhesive layer. The properties of the resin film are shown in Table 1. Next, an adhesive layer (second adhesive layer) with a thickness of 25 μm is formed on the resin film using the adhesive obtained in Manufacturing Example 1 to obtain a polarizer with a phase difference layer. It should be noted that until the evaluation, a polyethylene terephthalate film (PET film, diaphragm) with a thickness of 38 μm treated with a silicone-based release agent is bonded to the second adhesive layer. The results are shown in Table 2.
[0152] [Table 1]
[0153]
[0154] [Example 2]
[0155] <Production of Phase Difference Layer 2>
[0156] 20 parts by weight of a side chain liquid crystal polymer represented by the following chemical formula (the numbers 65 and 35 in the formula represent the molar % of the monomer unit, and for convenience, it is represented by a block polymer: weight average molecular weight 5000), 80 parts by weight of a polymerizable liquid crystal showing a nematic liquid crystal phase (manufactured by BASF: trade name Paliocolor LC 242) and 5 parts by weight of a photopolymerization initiator (manufactured by Ciba Specialty Chemicals: trade name Irgacure 907) were dissolved in 200 parts by weight of cyclopentanone to prepare a liquid crystal coating liquid. Then, the coating liquid was applied to a PET substrate subjected to a vertical alignment treatment using a rod coater, and then heated and dried at 80°C for 4 minutes to align the liquid crystal. The liquid crystal layer was irradiated with ultraviolet rays to cure the liquid crystal layer, thereby forming a phase difference layer (thickness 1 μm) showing a refractive index characteristic of nz>nx=ny on the substrate.
[0157]
[0158] The adhesive obtained in Manufacturing Example 2 was applied to the phase difference layer in a manner of 1 μm in thickness, and the phase difference layer 2 was bonded. Next, the substrate was peeled off from the phase difference layer 2, and the adhesive obtained in Manufacturing Example 2 was applied to the surface from which the substrate was peeled in a manner of 1 μm in thickness, and a resin film (manufactured by ZEON Corporation of Japan, trade name "ZEONOR FILM ZF14", thickness 13 μm) was bonded to the phase difference layer 2 via an adhesive layer. In addition, the same operation as in Example 1 was performed to obtain a polarizing plate with a phase difference layer. The results are shown in Table 2.
[0159] [Example 3]
[0160] A resin film (manufactured by Japan ZEON Corporation, trade name "ZEONOR FILM ZF14", thickness 13 μm) is laminated on the first adhesive layer. In addition, the adhesive obtained in Manufacturing Example 2 is applied in a manner of 1 μm in thickness to laminate the phase difference layer 1 and the phase difference layer 2 to prepare a phase difference layer laminate. The adhesive obtained in Manufacturing Example 2 is applied in a manner of 1 μm in thickness on the resin film laminated to the polarizer, and the first phase difference layer side of the phase difference layer laminate is laminated. Next, an adhesive layer (second adhesive layer) having a thickness of 25 μm is formed on the phase difference layer 2 using the adhesive obtained in Manufacturing Example 1. In addition, the same operation as in Example 1 is performed to obtain a polarizer with a phase difference layer. The results are shown in Table 2.
[0161] [Example 4]
[0162] In Example 2, the adhesive obtained in Manufacturing Example 2 was applied to the resin film bonded to the phase difference layer 1 in a manner of 1 μm in thickness, the phase difference layer 2 prepared in Example 2 was bonded, and an adhesive layer (second adhesive layer) having a thickness of 25 μm was formed on the phase difference layer 2 using the adhesive obtained in Manufacturing Example 1. A polarizing plate with a phase difference layer was obtained in the same manner as in Example 1. The results are shown in Table 2.
[0163] (Comparative Example 1)
[0164] The results are shown in Table 2, except that the resin film was not laminated on the phase difference layer 1, a polarizing plate with a phase difference layer was obtained in the same manner as in Example 1.
[0165] (Comparative Example 2)
[0166] The results are shown in Table 2, except that the second pressure-sensitive adhesive layer was formed on the phase difference layer 2 without laminating the resin film, the same procedure as in Example 2 was carried out to obtain a polarizing plate with a phase difference layer.
[0167] (Comparative Example 3)
[0168] The polarizing plate with a retardation layer was obtained in the same manner as in Example 2 except that the resin film was laminated via a 5 μm thick adhesive layer formed by using the adhesive obtained in Production Example 1 instead of the adhesive.
[0169] (Comparative Example 4)
[0170] The polarizing plate with a retardation layer was obtained in the same manner as in Example 3 except that the resin film was laminated via a 5 μm thick adhesive layer formed by using the adhesive obtained in Production Example 1 instead of the adhesive.
[0171] [Table 2]
[0172]
[0173] [evaluate]
[0174] As can be seen from Table 2, the polarizing plates with a retardation layer according to the examples of the present invention suppress the occurrence of pits and have excellent display properties.
[0175] Industrial Applicability
[0176] The polarizing plate with a retardation layer according to the embodiment of the present invention can be suitably used in image display devices such as liquid crystal display devices, organic EL display devices, and inorganic EL display devices.
Claims
1. A polarizing plate with a phase difference layer, which comprises, in order: a polarizing plate including a polarizer, a first adhesive layer, an orientation solidified layer of a liquid crystal compound, i.e., a phase difference layer, and a second adhesive layer, A resin film is laminated on the phase difference layer via an adhesive layer.
2. The polarizing plate with a phase difference layer according to claim 1, wherein: The resin film is laminated on the second adhesive layer side of the phase difference layer.
3. The polarizing plate with a phase difference layer according to claim 1, wherein: The resin film is laminated on the first adhesive layer side of the phase difference layer.
4. The polarizing plate with a phase difference layer according to claim 1, wherein: The resin film is a cyclic olefin resin film.
5. The polarizing plate with a phase difference layer according to claim 1, wherein: The resin film has a refractive index distribution of nx=ny>nz.
6. The polarizing plate with a phase difference layer according to claim 1, wherein: The Re(550) of the phase difference layer is 100nm-190nm, the Re(450) / Re(550) is less than 1, and the angle between the slow axis of the phase difference layer and the absorption axis of the polarizer is 40°-50°. 7 . The polarizing plate with a retardation layer according to claim 1 , further comprising a retardation layer having a refractive index distribution of nz>nx=ny. 8 . An image display device comprising the polarizing plate with a retardation layer according to claim 1 . 9 . The image display device according to claim 8 , which is an organic electroluminescent display device.
Citation Information
Patent Citations
Paper transporting roller
JP1979014738A
Optically active liquid crystal compound having cyano group
JP1989070455A
Protective film for polarizer and its manufacturing method
JP2001343529A
Homeotropic alignment liquid-crystalline composition, method for producing homeotropic alignment liquid crystal film and homeotropic alignment liquid crystal film
JP2002333642A
Pressure-sensitive adhesive for optical film, pressure-sensitive adhesive layer for optical film, its manufacturing method, pressure-sensitive adhesive optical film and image display device
JP2006183022A